2017
DOI: 10.1111/opo.12372
|View full text |Cite
|
Sign up to set email alerts
|

A proposed minimum data set for international primary care optometry: a modified Delphi study

Abstract: Purpose: To identify a minimum list of metrics of international relevance to public health, research and service development which can be extracted from practice management systems and electronic patient records in primary optometric practice. Methods: A two stage modified Delphi technique was used. Stage 1 categorised metrics that may be recorded as being part of a primary eye examination by their importance to research using the results from a previous survey of 40 vision science and public health academics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…From a health-care provider's perspective, it is easier to analyze the data fields that are compulsory options rather than free-text data. [ 27 28 ] To compliance with data quality criteria such as data consistency and comparability in COVSS, not only a COVID-19 MDS but also more detailed categories (levels) and data formats for data capturing were defined.…”
Section: Discussionmentioning
confidence: 99%
“…From a health-care provider's perspective, it is easier to analyze the data fields that are compulsory options rather than free-text data. [ 27 28 ] To compliance with data quality criteria such as data consistency and comparability in COVSS, not only a COVID-19 MDS but also more detailed categories (levels) and data formats for data capturing were defined.…”
Section: Discussionmentioning
confidence: 99%
“…From the physicians' point of view, it is easier to analyze the data elements that are compulsory options rather than free text data. [ 38 ] In this study, the designed registry system has been convenient and reliable, and even manual data entry has been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Davey et al stated that MDS should be easily integrated into clinical practice and should not be mistaken for a clinical guideline and should not add workload to the clinicians. [ 23 ] Hawes et al showed that an MDS provides considerable improvement in the accuracy and comprehensiveness of the information in residents’ medical records, affects the comprehensiveness of the care plan, care quality, and life quality, and reduced the duration of hospitalization[ 24 ]…”
Section: Discussionmentioning
confidence: 99%